Successful Plant Growth-Promoting Microbes: Inoculation Methods and Abiotic Factors - Lopes, Monyck Jeane dos Santos; Dias-Filho, Moacyr Bernardino; Gurgel, Ely Simone Cajueiro (Frontiers in Sustainable Food Systems, 2021)
Plant-microbe interactions have been the subject of several biotechnological studies, seeking sustainable development and environmental conservation. The inoculation of plant growth-promoting microbes (PGPM) in agricultural crops is considered an environmental-friendly alternative to chemical fertilization. Microbial inoculants are mainly inoculated onto seeds, roots and soil. PGPM improve plant growth by enhancing the availability of nutrients, the regulation of phytohormones, and by increasing plant tolerance against biotic and abiotic stresses. One of the main obstacles with PGPM research are the inconsistent results, which may be the result of inoculation methods and abiotic factors, such as soil (nutrient or heavy metal contents and pH), water availability, light intensity and temperature. This review addresses how the PGPM inoculants act on plant growth, what mechanisms they use to survive under stressful environmental conditions, and how inoculation methods and abiotic factors can interfere on the success of microbial inoculation in plants, serving as a basis for research on plants-microorganisms interaction.